Service Marketing Model Influencing Consumer’S Buying Decision of Healthy Cereal Bakery in Bangkok Area - Wiroonsri, Prajet; Waratornpaibul , Theerawee; Sengsuebphol, Narupon (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aimed 1) to study the factors of personal characteristics influencing the consumers’ purchase decision, and 2) to study the factors of marketing for services influencing the consumers’ purchasing decision of healthy cereal bakery in Bangkok. Data were collected with quantitative research. A questionnaire was the research instrument. The samples consisted of 400 respondents who had experience in purchasing Healthy cereal bakeries in Bangkok. The statistics used for data analysis were One-way ANOVA, Pearson’s Product Moment Correlation coefficient, and Multiple Regression Analysis. The findings revealed that the factors of personal characteristics in occupation, status, and income per month affect the consumers’ purchasing decision of healthy cereal bakery in Bangkok region at a statistically significant level .05. And the factors of marketing for services influencing consumers’ purchasing decision of healthy cereal bakery in Bangkok region were product, place, promotion, physical evidence, and process at statistically significant level .05.and the influencing factors were effective at 46.40 percent.